(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article reveals the role of correspondence in establishing diplomatic relations. It emphasizes the importance of the effect of correspondence with the formation and development of these relations. Experience has shown that the assumptions in the correspondence inaccurate and misunderstood expression lead to a worsening of relations between states. However, the correspondence is able to clear up misunderstandings, and it brought by an apology, to prevent clashes and war, restore peace and harmony. Therefore, when correspondence is necessary to be extremely careful and to avoid even the slightest mistake. Having considered the rulers of the historically established relationships, it can be concluded that their policies, as well as to the correspondence had a significant impact on their position among other countries and future development.